Management of Patients with Atresia: Factors Affecting Survival - Khan, Kifayat; Ullah, Hazrat; Rehman, Fazal (Journal of Postgraduate Medical Institute, 2011)
A total of 75 newforn patients with jejunoileal atresia were studied during 4 year period from August 1993 to July 1997. All the patients were delivered at home with fullterm gestation period spontaneously and were admitted through emergency to the department of paediatric surgery PGMI/LRH, Peshawar. there were 35 (46.66%) male babies and 40 (53.33%) female babies. mean birth wegith was 2.45kg with 25(33.33%) patients less than 2.5kg and 50(66.66%) patients 2.5 - 3kg. sixty (80%) patients presented between 2 - 5 days of age while 15(20%) presented at the age of more than 5 days. bilious vomiting was present in all (100%) patietns. Abdominal distension in 50(66.66%) patietns. constipation in 54 (72%) and jaundice in 9 (12%) patients. Maternal history of polyphydramnios was present in 30 (40%) patients. Twenty one (28%) patients were having associated hypothermia. thirty five out of seventy five patients were having jejunal atresia while 40 had ileal atresia. Type IIIa and II were the most common type of atresia which were found in 30 (40%) & 24 (32%) of patients respectively. fifty four patients were treated by primary bowel anastomosis and 21 with temporary enterostomies. Thirty (55.55%) patietns died postoperatively in the group treated by primary bowel anastomosis while no patients died from the group of patients treated by enterostomies.